Scientific Research in Homeopathic Medicine: Validation, Methodology and Perspectives. Issue 2 (2007) - Pitari, Giuseppina
Abstract : Verona's School of Homeopathic Medicine (www.omeopatia.org) organized a day of full immersion in the field of homeopathy, focusing on the validity of this much-debated discipline. There is widespread consensus in the medical community that evidence-based medicine is the best standard for assessing efficacy and safety of healthcare practices, and systematic reviews with strict protocols are essential to establish proof for various therapies. Students, homeopathic practitioners, academic and business representatives, who are interested in or curious about homeopathic practices attended the conference.